2017
DOI: 10.30935/cedtech/6186
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Students on Acceptance of Tablets and Self-directed Learning with Technology

Abstract: Recent mobile learning technologies offer the opportunity for students to take charge of the learning process both inside and outside the classroom. One of these tools is the tablet PC (hereafter 'tablet'). In parallel with increased access to e-content, the role of tablets in learning has recently begun to be examined. This study aims to reveal the relationship between the level of acceptance of tablets (TAM) and the level of selfdirected learning with technology (SDLT) of students and to differentiate these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
2
20
1
2
Order By: Relevance
“…Likewise, Çelik et al ( 2012 ) found no statistically significant differences regarding male and female participants’ use of ICT for self-regulated learning. The current study is also aligned with Eroglu and Ozbek ( 2018 ), who found out that students’ self-directed technology-based learning and students’ attitude towards e‐learning do not differ in terms of gender (p. 305), as well as with Gokcearslan ( 2017 ), who reported that no meaningful difference was found in the level of self-directed learning with technology in terms of gender. Contrary to current study findings, some research revealed significant gender-related differences in perceptions, motivation, and usefulness of this type of learning (e.g.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Likewise, Çelik et al ( 2012 ) found no statistically significant differences regarding male and female participants’ use of ICT for self-regulated learning. The current study is also aligned with Eroglu and Ozbek ( 2018 ), who found out that students’ self-directed technology-based learning and students’ attitude towards e‐learning do not differ in terms of gender (p. 305), as well as with Gokcearslan ( 2017 ), who reported that no meaningful difference was found in the level of self-directed learning with technology in terms of gender. Contrary to current study findings, some research revealed significant gender-related differences in perceptions, motivation, and usefulness of this type of learning (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…According to Gokcearslan ( 2017 ), the level of self-directed learning is a predictor of the integration of technology. To motivate students to self-directedly use technology for learning, teachers need to use different types of support, such as behavior support (enhancing confidence in their abilities to engage in out-of-class learning activities), capacity support (helping learners to develop the capacity to use the resources effectively), or pedagogical or metacognitive guidance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers, reddy et al [48], Sakarji et al [54],Cacciamani et al [55], Joo [56] and Lai [57] state that an individual must have relevant computing skills to use a given technology and continue using the given technology. Literature also showed over the years that the most common literacy associated with digital literacy was computer literacy [32][7][20] [58]. 4 shows that all the variables range from 0.827 -0.881, with no significant difference between them.…”
Section: Levelsmentioning
confidence: 99%
“…The use of ICTs in classroom activities results in classes that are more active and more participative, producing greater motiva-tion [40,41]. However, some authors also indicate that students prefer not using tablets in class because they distract them [42].…”
Section: Effects Of Technology On Motivationmentioning
confidence: 99%